THE APPLICATION OF THE ROLEPLAYING METHOD TO INCREASE THE LEARNING ACTIVITY OF STUDENTS IN FIQH SUBJECTS - Muhamad Khoiri, Muzakki; Lisnawati, Santi; Sinta Dewi, Reni (Al-Mubin, 2025)
This research aims to increase students' learning activity in Fiqh lessons through the role playing method in class X-7 MAN 1 Bogor Regency. This study uses the Classroom Action Research (PTK) method which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subject of the study is 36 students in grades X-7 in the even semester of the 2025 school year. Student activity was measured using observation sheets in each cycle. The results showed an increase in learning activity in cycle I by 61% (Moderately Active), and increased in cycle II to 87% (Very Active). In conclusion, the role playing method can increase students' learning activity in Fiqh lessons in grades X-7